Core-Etched CC/SnO2 Nanotube Arrays as High-Performance Anodes for Lithium-Ion Batteries With Ionic Liquid Electrolyte - Shen, Ao; Zhang, Ziying; Zhang, Huizhen; Zhao, Yangqiang; Xu, Pingping; Zhou, Yangyang; Weng, Ying (Frontiers in Materials, 2020)
Despite the design of nano-structured SnO2 anodes has attracted much attention because of its high theoretical capacity, good electron mobility and low potential of lithium-ion intercalation, challenges remain due to their weak mechanical stability, complex processing and rapid capacity decay. The flexible one-dimensional binder-free porous CC/SnO2 nanotube arrays are synthesized with a well-suited core etching method to meet the needs of steady operation of flexible devices under mechanical deformation. This porous, binder-free nanostructure has large contact area with the electrolyte and excellent electron transport performance. The electrochemical measurements demonstrate that these nanotube arrays have high energy density and high-rate capability. After 500 cycles at a current density of 200 mA g−1, their stable capacity remains at 595.7 mA h g−1.